APLIKASI SISTEM PENDUKUNG KEPUTUSAN PEREKRUTAN CALON PEGAWAI NEGERI SIPIL (CPNS) DI KEMENTERIAN PERDAGANGAN RI PADA TES KOMPETENSI BIDANG (TKB) DENGAN - Ningrum, Rahma Farah (PETIR, 2015)
Designing an application decision support system using ANP (Analytical Network Process) at this stage of recruitment of civil servants is not easy, should be aligned with the procedures that have been set by national civil servant recruitment committee or department. Stages selecting employess that will register as an employee in the Ministry of Trade consists of administrative selection Basic Competence Test (TKD), and Competency Test Field (TKB). To produce a valid screening employees, required measurable decision-making based on the results of the amalgamation of several existing tests. To design the application in writing is done with the waterfall method by combining the methods of ANP (Analytical Network Process) as measurement data validity of the tests conducted. Methods ANP (Analytical Network Procees) to represent the degree of importance some of the results of tests conducted by considering the relationship between the criteria. ANP (Analytical Network Process) combines some of the assessments into one logical way. And the results obtained from this screening is a candidate for employee data sorting used as an alternative in the decision so that the recruitment process can take place effectively and efficiently and to produce objective decisions.